Amygdala but not hippocampal damage associated with smaller social network size. (9th September 2022) - Beadle, Janelle N.; Heller, Abi; Rosenbaum, R. Shayna; Davidson, Patrick S.R.; Tranel, Daniel; Duff, Melissa
Abstract: Social network size has been associated with complex socio-cognitive processes (e.g., memory, perspective taking). Supporting this idea, recent neuroimaging studies in healthy adults have reported a relationship between social network size and brain volumes in regions related to memory and social cognition (e.g., hippocampus, amygdala). Lesion-deficit studies in neurological patients are rare and have been inconclusive due to differences in participant sampling and measurement. The present study uses a multiple case study approach. We investigated patients with focal damage to the hippocampus and/or amygdala (two neural structures thought to be critical for social networks), and examined the patients' social network size, loneliness, and life satisfaction relative to a non-injured comparison group. Patients with amygdalar damage had smaller social networks and reported higher levels of loneliness and lower life satisfaction, on average, than comparison participants. Patients with damage to the hippocampus reported more friends than the comparison participants, but did not differ in their ratings of loneliness or life satisfaction. This lesion study offers new evidence that the amygdala is critical for social networks, life satisfaction, and reduced loneliness.